Future Distribution of Suitable Habitat for Pelagic Sharks in Australia Under Climate Change Models - Birkmanis, Charlotte A.; Freer, Jennifer J.; Simmons, Leigh W.; Partridge, Julian C.; Sequeira, Ana M. M. (Frontiers in Marine Science, 2020)
Global oceans are absorbing over 90% of the heat trapped in our atmosphere due to accumulated anthropogenic greenhouse gases, resulting in increasing ocean temperatures. Such changes may influence marine ectotherms, such as sharks, as their body temperature concurrently increases towards their upper thermal limits. Sharks are high trophic level predators that play a key role in the regulation of ecosystem structure and health. Because many sharks are already threatened, it is especially important to understand the impact of climate change on these species. We used shark occurrence records collected by commercial fisheries within the Australian continental Exclusive Economic Zone (EEZ) to predict changes in future (2050 to 2099) relative to current (1956 to 2005) habitat suitability for pelagic sharks based on an ensemble of climate models and emission scenarios. Our predictive models indicate that future sea temperatures are likely to shift the location of suitable shark habitat within the Australian EEZ. On average, suitable habitat is predicted to decrease within the EEZ for requiem and increase for mackerel sharks, however, the direction and severity of change was highly influenced by the choice of climate model. Our results indicate the need to consider climate change scenarios as part of future shark management and suggest that more broad-scale studies are needed for these pelagic species.